Kesenjangan Upah Antar Gender di Kerinci: Tinjauan Hukum Islam dan Hukum Positif - Darwis, Ninil Aninda; Dhuasha, Wilda (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2022)
The practice of the farm labor wage system in Siulak Panjang Village, the determination of wages for farm laborers refers to the concept of gender equality, where the wages determined must be based on the quality of one's work, so that there is no discrimination in labor wages. Payment of wages is carried out after the laborer's work is completed, which is the basis for payment of wages is what generally occurs in the Siulak Panjang Village community. This research is a field research with the model used in this research is qualitative research (getting information and data directly in the field). This data collection technique revealed that data analysis is the process of searching, arranging systematically transcripts of research results pointing out, The factors of the difference in wages between male and female farm laborers are caused by: factors of work time, physical, and workload The Siulak Panjang Village community is in accordance with Islamic law and every muamalah is permissible, if mu'ajir gives a difference in wages between male and female farm laborers on the basis that female farm laborers often come late, men are more responsible for making a living for their families and the majority of men do their work faster. The positive law that applies in Siulak Panjang Village is based on Law Number 13 of 2003. Based on this positive law, wages are usually determined by both parties in a work agreement, in employer regulations, in wage regulations, or in a labor agreement